Glucocorticoid insensitive asthma: a one year clinical follow up pilot study. Issue 12 (1st December 1998) - Demoly, Pascal; Jaffuel, Dany; Mathieu, Marc; Sahla, Hocine; Godard, Philippe; Michel, François-Bernard; Bousquet, Jean
Abstract : BACKGROUND: Glucocorticoid resistant or insensitive asthmatic subjects are usually defined as patients whose baseline pre-bronchodilation forced expiratory volume in one second (FEV1 ) of less than 70–80% predicted improves significantly in response to β2 agonists but by less than 15% following 1–2 weeks of 40 mg prednisolone daily. Since there is little long term clinical information on these patients, a one year prospective study was performed to assess whether glucocorticoid sensitivity may vary over time. METHODS: Nineteen severe asthmatic subjects were studied and received 40 mg prednisolone daily for seven days. Prednisolone was given for a further seven days in glucocorticoid insensitive asthmatics and then stopped. Patients were followed up for one year and the glucocorticoid test was repeated on five patients in each group six months later. RESULTS: Eleven patients were classified as glucocorticoid insensitive and eight as glucocorticoid sensitive on day 7. The demographic characteristics of the patients were similar in both groups. Four glucocorticoid insensitive patients became responsive after one further week of prednisolone treatment. Six months later, four of five glucocorticoid sensitive patients and three of five previously glucocorticoid insensitive patients were glucocorticoid sensitive. CONCLUSIONS: Glucocorticoid sensitivity varies over time.